Strategies to Minimize Students’ Learning Obstacle in Fractions: A Grounded Theory - Isnawan, Muhamad Galang; Suryadi, Didi; Turmudi, Turmudi (FKIP Universitas Lampung, 2022)
Fractions are a fundamental mathematical concept that is quite important for life. However, the existing facts prove that fraction concepts in mathematics are a problem that has become a learning obstacle for students in schools. Therefore, this study aims to find alternative strategies to minimize the learning obstacle. The researcher then used a grounded theory design to find this strategy. Researchers also combined research design with phenomenology to find the core categories. Researchers used systematic analysis (open, axial, and selective), combined with thematic analysis with NVivo-12. The analysis results revealed that ontogenic in the form of participants were unable to simplify, determine equivalent fractions, and carelessness was the most significant learning obstacle. The strategy obtained was the use of a didactic design based on a didactical situation in collaboration with didactical design research, which would minimize student learning barriers on fractions.Keywords: fractions, learning obstacle, grounded theory, phenomenology, didactical situation.DOI: http://dx.doi.org/10.23960/jpmipa/v23i1.pp87-99